PENDIDIDIKAN EMANSIPATORIS DAN MASYARAKAT MADANI - Rukiyati Rukiyati; L. Andriyani L. Andriyani (LPMPP Universitas Negeri Yogyakarta, 1999)
The civil society is basically a society which is dialogueorientedand emancipato ya s well as independent in natuse.It is an arena where various social movements express themselvesin groups to proceed with their interests.'Fo come to such a society there needs to be a socialtransformation which involves, among others, education.All this time the educational realities in Indonesia have notheen adequate fol the formation of the cibil society. 1 herefore,there needs to be a refosniation of the educational pal adigmso that education which is emancipato ? iu nature isachieved. Habermas' theory of co ununicationc an be onealternative means in the course of reforming the educationalparadigm in Indonesia.The imple nentationo ft laber nas't heory of communicationin education can be made in the teaching-learningprocess. This process demands the fulfillment of the claimsof communication concerning tr 1t1-r1i.g htness. sincerity, andcomprehensibility. In the teaching-learning process whichfdfils the claims of comnlunication will appear the dimensionsof interest, discourse. consensus, and emancipationwhich bring the teacher and students together to a self-I eflection.